A review of eosinophilic gastroenteritis. - Baig, Muhammad Ahsan (National Medical Association, 2006)
Eosinophilic gastroenteritis (EG) is a rare disease of unknown etiology characterized by patchy or diffuse eosinophilic infiltration of the gastrointestinal tract wall with various gastrointestinal manifestations. As clinical presentation and radiological findings in EG are nonspecific, diagnosis requires a high index of suspicion and exclusion of other disorders that are associated with peripheral eosinophilia. This article reviews the history, current concepts of this complex disorder and the common symptoms. Because there is no gold standard for this disease, a wide variety of diagnostic criteria is presented.